Legal provisions 1 (Infonavit, 1976)
The establishment of the Workers' National Housing Fund Institute, an organization created to solve the housing problema of that large section of the Mexican population, was preceded by important legislative amendments. The first of these amendments was a bill submitted by the President of the Republic to the House of Representatives of the Congress of the Union on December 22, 1971, so as to modify the contents of Section XII of Paragraph